The Effects Of Iron And Phosphorus Applications On The Yield and Yield Components In Chickpea (Cicer arietinum L.) - Yunus AKTAS; Necat TOĞAY (ISPEC Journal of Agricultural Sciences)
The research was conducted to determine effects of different levels of iron and phosphorus on the yield and some yield components in chickpea in 2017 in Van ecological conditions. The experiment was laid out in a factorial randomized block design with three replications. The doses were used phosphorus (0, 4 and 8 kg da-1) and iron (0, 1 and 2 kg da-1) in this study. In the study were investigated the plant height, first pod height, branch number per plant, pod, seed number and per plant, seed number per pod, biological yield, seed yield per unit, harvest index, 100-seed weight, protein ratio phosphorus content in seed, phosphorus content in seed and number of nodule. The results of the study indicated that iron and phosphorus applications increased significantly the seed yield and yield components. While the highest seed yield was obtained from 4 kg phosphorus /da + 1 kg iron /da application with 160.4 kg/da, the lowest seed yield was obtained from control parcels with 113.3 kg da-1.